Tendências no comportamento de compra do consumidor carioca: um estudo do perfil dos consumidores cariocas de moda para a década de 2020 - Moreira, Gabriela Pinto Stocco (2019)
The present study aims to identify the buying motivation of female young residents of the south zone of Rio de Janeiro in regards to fashion. When analyzing the factors related to the decision to buy fashion brands by this group, the research aims to design the profiles of this consumer, in order to help the positioning, in the coming years, of brands aimed at this public. The research was based on studies on Consumption and Trends, and qualitative methods (interviews and focus groups) were used to finally identify three different profiles of female consumers.It is believed that the study will contribute to the consolidation of the field of Creative Economy in Brazil, since it is still being constructed. It is also worth noting that, within this field, fashion is an important segment, especially considering its adherence to the identity of the city of Rio de Janeiro. According to data from Firjan, it is Rio de Janeiro, among the four largest Brazilian fashion exporting states, which adds greater value to the fashion products that leave the country. And, according to Sebrae-RJ data, the sector should grow 5.6% in that state, until 2023, which justifies thinking about the positioning of brands for the next decade